Oxidative stress and inflammation regulation of sirtuins: New insights into common oral diseases - Pan, Zijian; Dong, Hao; Huang, Ning; Fang, Jie (Frontiers in Physiology, 2022)
Sirtuins are a family of nicotinamide adenine dinucleotide (NAD)+-dependent histone deacetylases, comprising seven members SIRT1-SIRT7. Sirtuins have been extensively studied in regulating ageing and age-related diseases. Sirtuins are also pivotal modulators in oxidative stress and inflammation, as they can regulate the expression and activation of downstream transcriptional factors (such as Forkhead box protein O3 (FOXO3a), nuclear factor erythroid 2-related factor 2 (Nrf2) and nuclear factor-kappa B (NF-κB)) as well as antioxidant enzymes, through epigenetic modification and post-translational modification. Most importantly, studies have shown that aberrant sirtuins are involved in the pathogenesis of infectious and inflammatory oral diseases, and oral cancer. In this review, we provide a comprehensive overview of the regulatory patterns of sirtuins at multiple levels, and the essential roles of sirtuins in regulating inflammation, oxidative stress, and bone metabolism. We summarize the involvement of sirtuins in several oral diseases such as periodontitis, apical periodontitis, pulpitis, oral candidiasis, oral herpesvirus infections, dental fluorosis, and oral cancer. At last, we discuss the potential utilization of sirtuins as therapeutic targets in oral diseases.